2008
DOI: 10.1158/0008-5472.can-08-0320
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Relationship between O6-Methylguanine-DNA Methyltransferase P140K Expression Level and Chemoprotection of Hematopoietic Stem Cells

Abstract: Retroviral-mediated delivery of the P140K mutant O6-methylguanine-DNA methyltransferase (MGMTP140K) into hematopoietic stem cells (HSC) has been proposed as a means to protect against dose-limiting myelosuppressive toxicity ensuing from chemotherapy combining O6-alkylating agents (e.g., temozolomide) with pseudosubstrate inhibitors (such as O6-benzylguanine) of endogenous MGMT. Because detoxification of O6-alkylguanine adducts by MGMT is stoichiometric, it has been suggested that higher levels of MGMT will aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 41 publications
2
25
1
Order By: Relevance
“…This implies that increased amounts of MGMT P140K protein are not required for efficient protection against DNA damage induced by alkylating drugs. This result is in line with the findings by Milsom et al 26 demonstrating that in contrast to a strong viral promoter a weaker cellular promoter was sufficient for an in vivo protection after treatment with BCNU or TMZ.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This implies that increased amounts of MGMT P140K protein are not required for efficient protection against DNA damage induced by alkylating drugs. This result is in line with the findings by Milsom et al 26 demonstrating that in contrast to a strong viral promoter a weaker cellular promoter was sufficient for an in vivo protection after treatment with BCNU or TMZ.…”
Section: Discussionsupporting
confidence: 92%
“…66 Comparison of a strong viral and a weaker cellular promoter revealed that use of the cellular promoter resulted in sufficient expression and detoxification efficiency of MGMT P140K protein and in better engraftment of transduced HSCs in mice. 26 Promoter methylation and silencing has been described as a disadvantage of the spleen focus-forming virus promoter, 67,68 which we used in our vector. To circumvent this problem, replacement of the spleen focus-forming virus promoter by the methylation-resistant ubiquitous chromatin opening element should enable stable and long-term expression of transgenes in HSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, mCherry expression from GV and LV bidirectional vectors did not differ but was 44 GV and LV bidirectional vectors were constructed harboring MGMT-P140K and eGFP in either orientation. We chose the modest human PGK promoter as high MGMT-P140K expression was shown to inhibit proliferation of hematopoietic stem/progenitor cells.…”
Section: Comparison Of Bidirectional To 2a and Ires-mediated Coexpresmentioning
confidence: 87%
“…We chose the modest human PGK promoter as high MGMT-P140K expression was shown to inhibit proliferation of hematopoietic stem/progenitor cells. 44 Pilot experiments performed with GV and LV vectors showed that only the expression of MGMT-P140K in sense orientation was strong enough to yield a large amount of double-positive cells (data not shown). When a murine myeloid progenitor cell line, 32D, was transduced with these vectors (Figure 5a According to the coexpressed eGFP (Figure 5c), GV and LV transduced cells could be stepwise enriched from 20 to 93% or 43 to 93% by increasing BCNU concentrations from 0 to 35 mM, respectively.…”
Section: Comparison Of Bidirectional To 2a and Ires-mediated Coexpresmentioning
confidence: 96%